2000
DOI: 10.1046/j.1365-2923.2000.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medical students' performance using the anaesthesia simulator

Abstract: Our pilot data suggest that the simulator is a reliable assessment method for medical students' performance. Further work may justify the inclusion of the simulator as an evaluation and education tool and expanded to incorporate learning objectives of other medical disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 11 publications
3
39
0
3
Order By: Relevance
“…D Di is sc cu us ss si io on n The HPS has not been demonstrated to be a superior tool for learning when compared to existing methods and further study regarding the validity of simulation performance assessments is needed. [3][4][5][6] Despite limited research involving the HPS, acquisition of this expensive technology has increased exponentially. Our search located 158 centres whereas in 1997, Shimada et al identified only 29 institutions involved in education and training of physicians in anesthesia and other specialties and allied medical professionals.…”
Section: Méthode : Une Recherche Sur Le Web a Permis De Localiser Lesmentioning
confidence: 99%
“…D Di is sc cu us ss si io on n The HPS has not been demonstrated to be a superior tool for learning when compared to existing methods and further study regarding the validity of simulation performance assessments is needed. [3][4][5][6] Despite limited research involving the HPS, acquisition of this expensive technology has increased exponentially. Our search located 158 centres whereas in 1997, Shimada et al identified only 29 institutions involved in education and training of physicians in anesthesia and other specialties and allied medical professionals.…”
Section: Méthode : Une Recherche Sur Le Web a Permis De Localiser Lesmentioning
confidence: 99%
“…34,35 A checklist assessment of performance on a human simulator did not correlate with clinical and written evaluations of performance during an anesthesia rotation. 15,35 However, it is likely that the simulation checklist is measuring a different skill area than more traditional types of assessment. In realty, we will probably need a combination of methods to assess the complex skills required to provide high-quality medical care.…”
Section: Assessment Of Competence Using Simulationmentioning
confidence: 99%
“…They also rated it as a ''very good'' evaluation tool. 15 The major advantage of simulation was noted to be the ability to ''practice without risk'' to the patient. 16 Simulation improves the acquisition and retention of knowledge compared with traditional lectures 17,18 or review methods.…”
mentioning
confidence: 99%
“…The ACRM curriculum, which was originally designed for anesthesiologists, is now applied to many areas of medicine and health care (Blum et al 2004). The purposes of full-scale simulation have been reported to apply for many purposes (Devitt et al 1998(Devitt et al , 2001Gaba et al 1998;Morgan & Cleave-Hogg 2000;Morgan et al 2001Morgan et al , 2003Morgan et al , 2004Forrest et al 2002;Rosenblatt & Abrams 2002;Weller et al 2003;Murray et al 2004). To improve the clinical…”
Section: Introductionmentioning
confidence: 99%